The Impact of Entrepreneurial Orientation, Reconfiguring Capability and Moderation of Environmental Turbulence on Export Performance of SMEs in Nigeria - Samson, Abiodun Tope (Journal of Economics and Behavioral Studies, 2015)
Entrepreneurial orientation encapsulate the firm –level process, practice and strategic orientation while dynamic capabilities view of firm consists of the structure routine and processes that constitute its ability to reconfigure its asset base to match the requirement of the changing environment. The aim of this research emanated from the fact that only few studies examined how entrepreneurial strategic orientation and reconfiguring capability impact on export performance of SMEs in turbulent environment. In order to fill this vacuum, this study delineated relationship among these constructs and employed PLS-SEM on data collected from 201 exporting SMEs in Nigeria. The findings of the study suggest that entrepreneurial orientation, reconfiguring capability, and environmental turbulent significantly related to export performance. Environmental turbulence moderates the relationship between entrepreneurial orientation, reconfiguring capability and export performance. This suggests that SMEs could benefit from reconfiguring and renewal of their asset base and act in response to opportunities and threat to realize first order transformation in growth and export performance. Besides, this study also provides research conclusion to the appropriateness of entrepreneurial orientation and reconfiguring capability when there is environmental turbulence and their lack of effectiveness when there is stability.